PENGARUH INTERAKSI SOSIAL DAN MANAJEMEN KEPEMIMPINAN DALAM UPAYA MENINGKATKAN KINERJA AWAK KAPAL DI DERMAGA TERMINAL PELABUHAN TELUK LAMONG TANJUNG PERAK SURABAYA - jurnalmap map; Supangat ÔÇÄ (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This study aims to determine whether the factors of social interaction and leadership management of the skipper at the Teluk Lamong port, Tanjung Perak, Surabaya, which are directly oriented to the relationship simultaneously (simultaneously) or individually (partially) have an influence on the performance of the ship on board. In addition to the above, between social interaction and leadership management of the skipper at the Teluk Lamong Port Terminal, Tanjung Perak Surabaya, which one has a dominant influence on the performance of the ship on board. By taking a sample of 50 crew members in the Teluk Lamong Port Terminal, Tanjung Perak Surabaya and using quantitative descriptive research methods, it is known that the social interaction factor and the leadership management of the skipper at Teluk Lamong Port Terminal Tanjung Perak Surabaya jointly have a significant effect on performance. crew on board. While individually, Social Interaction has a more significant effect on the performance of the crew and has a more dominant effect than the Master's leadership management variable. On the other hand, the management of the captain's leadership has no significant effect on the performance of the ship.